Prawo spadkowe w nieznanym projekcie kodeksu cywilnego - Moszyńska, Anna (Z Dziejów Prawa [czasopismo zamknięte], 2020)
In literature on the codification of the civil law in Poland after the WWII, the years 1950—1954 are a research gap. The preparation of the draft of the Civil Code in 1951 remains al- most an unknown fact. The aim of this article is to present the work on the last book of this draft and solutions adopted herein. It is worth paying a closer attention to them, as they formed a clear example of progressive stalinization and compulsory transplantation of the Soviet patterns. The circle of statutory heirs was significantly narrowed, the freedom of testation was heavily re- stricted. Testate succession became almost completely meaningless. Under the former name of “legitime”, a reserve system (a forced share) was introduced. Testator could dispose of only a half of his assets, the rest had to be preserved for the benefit of the forced heirs. The responsibility for debts had been limited in a way which caused a high risk for creditors. The hastily prepared draft contained many gaps and errors. However, the political climate was not conducive to taking into account the remarks made to the draft.